Genome-wide sequencing reveals microRNAs downregulated in cerebral cavernous malformations - Kar, Souvik; Bali, Kiran Kumar (Journal of molecular neuroscience, 2017)
Cerebral cavernous malformations (CCM) are vascular lesions associated with loss-of-function mutations in one of the three genes encoding KRIT1 (CCM1), CCM2, and PDCD10. Recent understanding of the molecular mechanisms that lead to CCM development is limited. The role of microRNAs (miRNAs) has been demonstrated in vascular pathologies resulting in loss of tight junction proteins, increased vascular permeability and endothelial cell dysfunction. Since the relevance of miRNAs in CCM pathophysiology has not been elucidated, the primary aim of the study was to identify the miRNA-mRNA expression network associated with CCM. Using small RNA sequencing, we identified a total of 764 matured miRNAs expressed in CCM patients compared to the healthy brains. The expression of the selected miRNAs was validated by qRT-PCR, and the results were found to be consistent with the sequencing data. Upon application of additional statistical stringency, five miRNAs (let-7b-5p, miR-361-5p, miR-370-3p, miR-181a-2-3p, and miR-95-3p) were prioritized to be top CCM-relevant miRNAs. Further in silico analyses revealed that the prioritized miRNAs have a direct functional relation with mRNAs, such as MIB1, HIF1A, PDCD10, TJP1, OCLN, HES1, MAPK1, VEGFA, EGFL7, NF1, and ENG, which are previously characterized as key regulators of CCM pathology. To date, this is the first study to investigate the role of miRNAs in CCM pathology. By employing cutting edge molecular and in silico analyses on clinical samples, the current study reports global miRNA expression changes in CCM patients and provides a rich source of data set to understand detailed molecular machinery involved in CCM pathophysiology.
Published online: 8 February 2017
Gesehen am 25.06.2018